Preliminary Design of the Wheelchair Elevation Support Unit (WES) - Khairi Azri Kamal Arifin; Mat Jusoh, Mohammad Azzeim; Sukarnur bin Che Abdullah; Helmi bin Rashid (International Journal of Integrated Engineering, 2024)
The Wheelchair Elevation Support Unit (WES) has been designed to be an additional mechanism that can be installed into a standard wheelchair to extend its function. This mechanical device helps rehabilitation patients gain the ability to stand, which common wheelchairs are unable to offer. In this research, the Engineering Design Process (EDP) was used to design the product. The design and finite element analysis (FEA) simulation were performed using Catia V5 to verify the reliability and safety of the product. As a result, a sub-assembly with an overall weight of 8 kg was achieved, capable of supporting users with up to 90 kg of weight. The maximum von Misses stress of 62.5 MPa with a total deformation of 2.23 mm was simulated when using the aluminum alloy (6061 T6) material. With a 4.96 safety factor, the selection of this material was considered safe and reliable, as it is lightweight and suitable for engineering applications, especially when combined with the frame structure of the wheelchair. With a fast and easy disassembly process, it is beneficial for the users to return the wheelchair to its standard type. In the future, further improvements will be made to optimize the design. With this additional mechanism featured in the wheelchair, hopefully it will be able to support the rehabilitation process of patients by allowing them to stand with less effort.